2005
DOI: 10.1097/01.wnn.0000160822.53577.2c
|View full text |Cite
|
Sign up to set email alerts
|

Is Schizophrenia Associated with Narcolepsy?

Abstract: Objective: To determine the nature of the relationship between schizophrenia-like psychosis and narcolepsy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 91 publications
(98 reference statements)
0
11
0
Order By: Relevance
“…An intriguing possibility is that intrusion or leakage of REM sleep events into waking may contribute to the gating impairments following prolonged SD. Accordingly, a similar process has been shown to underlie preattentional and attentional disorders in schizophrenia (Zarcone et al, 1969), as well as the psychotic manifestations in narcolepsy (Walterfang et al, 2005).…”
mentioning
confidence: 98%
“…An intriguing possibility is that intrusion or leakage of REM sleep events into waking may contribute to the gating impairments following prolonged SD. Accordingly, a similar process has been shown to underlie preattentional and attentional disorders in schizophrenia (Zarcone et al, 1969), as well as the psychotic manifestations in narcolepsy (Walterfang et al, 2005).…”
mentioning
confidence: 98%
“…[25][26][27] Other reports do not allow definitive conclusions of whether the association with psychosis is primary, or secondary to stimulant treatments. 25,[28][29][30] Psychotic symptoms in narcolepsy have been evaluated in three controlled studies. Two studied narcolepsy, schizophrenic patients, and control subjects, 31,32 while another studied narcolepsy patients versus matched controls.…”
Section: S C I E N T I F I C I N V E S T I G a T I O N Smentioning
confidence: 99%
“…A review article suggested that comorbidity of narcolepsy and schizophrenia is likely to be rare and sporadic. 5 Our study presents such a rare case, in a patient suffering from comorbidity of childhood-onset narcolepsy and adolescent-onset schizophrenia.…”
Section: Introductionmentioning
confidence: 96%